2020
DOI: 10.1161/circheartfailure.120.007264
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Complexity of Heart Failure Risk and Treatment in Black Patients

Abstract: Although care of patients with heart failure (HF) has improved in the past decade, important disparities in HF outcomes persist based on race/ethnicity. Age-adjusted HF-related cardiovascular disease death rates are higher for Black patients, particularly among young Black men and women whose rates of death are 2.6- and 2.97-fold higher, respectively, than White men and women. Similarly, the rate of HF hospitalization for Black men and women is nearly 2.5-fold higher when compared with Whites, with costs that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
126
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 185 publications
(133 citation statements)
references
References 97 publications
5
126
2
Order By: Relevance
“…28,30,31 A multitude of causes have been implicated in this outcome disparity including biological/genetic, societal (access to healthy lifestyle choices), and healthcare (insurance and guideline-directed medical treatment access) factors. 34 While no difference was detected between Black and White HM3 recipients with regards to the primary end point, the present study identified independent predictors of Black LVAD patient outcomes. Age >65 years was identified as an independent predictor of primary end point failure while better baseline renal function (estimated by estimated glomerular filtration rate) was demonstrated to predict primary end point success in our analysis.…”
Section: Discussioncontrasting
confidence: 64%
“…28,30,31 A multitude of causes have been implicated in this outcome disparity including biological/genetic, societal (access to healthy lifestyle choices), and healthcare (insurance and guideline-directed medical treatment access) factors. 34 While no difference was detected between Black and White HM3 recipients with regards to the primary end point, the present study identified independent predictors of Black LVAD patient outcomes. Age >65 years was identified as an independent predictor of primary end point failure while better baseline renal function (estimated by estimated glomerular filtration rate) was demonstrated to predict primary end point success in our analysis.…”
Section: Discussioncontrasting
confidence: 64%
“…Our patient population is truly diverse and mainly consisted of racial and ethnic minorities, with Black and Hispanic participants forming a majority—groups who can be under-represented in randomized multicenter studies. In addition, studies have shown that Black patients have a significantly higher rate of HFH [ 45 ]. Representation of this population in our study is therefore relevant and complements the results of randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…FI may pose a higher cardiovascular risk for racial and ethnic minorities, relative to their NHW counterparts, due to the generally higher rates of clinical risk factors such as diabetes, hypertension, and obesity, all of which contribute to worse cardiovascular outcomes [ 63 ]. Structural barriers, such as socioeconomic inequality, educational disparities, and bias and discrimination in healthcare, as well as historical practices like redlining – which subjects Black and other under-represented racial/ethnic populations to discrimination in housing – have been reported to contribute to the disproportionately higher rates of cardiovascular risk factors and CVD among racial/ethnic minorities, compared to NHW individuals [ 64 , 65 ].…”
Section: Food Insecurity and Cvdmentioning
confidence: 99%